U.S. Multinationals and Preferential Market Access - Emily Blanchard; Xenia Matschke (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2010)
This paper examines the relationship between offshoring activity by U.S. multinational firms and the structure of U.S trade preferences. We combine firm level panel data on U.S. foreign affiliate activity from the U.S. Bureau of Economic Analysis (BEA) with detailed measures of U.S. trade preferences from the U.S. International Trade Commission (USITC) to create a three-way panel that spans 80 industries, 184 countries, and ten years (1997-2006). Consistent with existing theory, we find that off- shoring and preferential market access are positively and consistently correlated, both in the pooled sample and within countries, industries, and years. Using both instrumental variables and simultaneous equations approaches to address the endogeneity of export-oriented foreign investment, we find that a 10% increase in U.S. foreign affiliate exports to the U.S. from a particular industry and country is associated with a 4 percentage point increase in the rate of preferential duty-free access. Restricting attention to the Generalized System of Preferences (GSP) among potentially eligible developing countries, we find that the influence of multinational affiliate sales on preferential market access more than triples.
Keywords: 330